Upaya Pengendalian Tekanan Darah Tinggi Dengan Penerapan Terapi Komplementer Pada Lansia Hipertensi - Aneng Yuningsih; Yayi Siti Haeriyyah; Fenty Rosmala; Sri Susilawati; Ide Suhendar (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: One of the very basic problems in the elderly is health problems due to degenerative processes. The prevalence of health problems that many elderly suffer include hypertension. Hypertension is often referred to as the silent killer because it can attack anyone suddenly and can result in death. Hypertension is also at risk of causing various other diseases, such as heart failure, coronary heart disease, kidney disease and stroke, so that treatment must be done immediately before complications and other adverse consequences occur such as reducing the life expectancy of sufferers. One way to treat hypertension which has low side effects is non-pharmacological treatment/complementary therapy. Objective: The participants in this activity totaled 58 elderly people with an age range of 60 years and over Method: The implementation of community service is carried out through the stages: Preparation, Socialization, Implementation of Activities (Explanation of material, Discussion and Evaluation) and closing. Result: Based on the results of calculating the pre-test and post-test values of providing education, it was found that there was a significant increase in the knowledge of the elderly, from an average pre-test value of 38.10 to 88.10, the average post-test value had occurred increase in post-test results by 50, with the highest score in the post-test being 100 (as many as 7 people). Conclusion: Based on the results of the evaluation of Community Service activities, an overview of the understanding of efforts to control blood pressure through complementary therapy in the elderly with hypertension after being given education has increased significantly